PENGUATAN STRATEGI PEMASARAN DI TENGAH PANDEMI COVID-19 DEMI BERKELANJUTAN UKM KECAMATAN SEMAMPIR KOTA SURABAYA (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2021)
During the Covid-19 pandemic, which is still happening in Indonesia today, all business lines, both large, medium and small scale, were affected by the economy and society. The real impact of Small and Medium Enterprises (SMEs) is a drastic decline in sales, especially UKM players in Semampir District, Surabaya City. So, they need assistance from academicians from the Sekolah Tinggi Ilmu Ekonomi Indonesia (Stiesia) Surabaya in order to businesses can survive amid the Covid-19 pandemic. Assistance from Stiesia Surabaya academicians by providing strengthening business strategies by analyzing external and internal factors that influence the development of SMEs by adopting the Strength, Weakness, Opportunity and Threat (SWOT) analysis method. Based on the SWOT analysis, it produces several recommendations for SMEs in Semampir District, Surabaya City, namely: (1). Make the most of online business sales (social media and online communication facilities), (2). Having an alternative business venture needed by consumers during the Covid-19 pandemic, (3). Collaborating with other SMEs owners in producing products that are suitable for consumers during the Covid-19 pandemic. The conclusion is that SMEs owners should make adaptations, innovations and creativity so that SMEs businesses can survive during the Covid-19 pandemic.